Corneal Endothelial Morphology in Type II Diabetic versus Non-Diabetic Individuals using Specular Microscopy - Shrestha, Suhana; Shrestha, Poonam; Gurung, Chandra Maya (Nepalese Journal of Ophthalmology, 2026)
Introduction: Diabetes is one of the major causes of comorbidities in elderly patients. Impaired vision and blindness in chronic diabetic population occurs due to poor corneal wound healing, corneal oedema, and other abnormalities of corneal layers as a result of accumulation of toxic products within cornea. Literature has shown corneal endothelial changes in diabetes in different populations but study on the Nepali population is sparse. Objective: To compare the corneal endothelial parameters between type II diabetics and non-diabetics. Methodology: A hospital-based, analytical, cross-sectional study was conducted after ethical approval from 2022 January to 2023 June using a CEM 530 NIDEK Spectral microscope to analyse the Endothelial Cell Density (ECD), Central Corneal Thickness (CCT), Hexagonality (HEX), and Coefficient of Variance (CoV). After meeting the selection criteria, 74 type II diabetic cases and 74 (age and sex-matched) controls were enrolled in this study using consecutive sampling method. Result: The ECD was relatively higher in OD of diabetics than controls (2756.3 ± 228 cells/mm2 vs. 2748.7 ± 279.4 cells/mm2). The CoV was significantly higher in diabetics (OD 32.5 ± 5.4; OS 32 ± 4.7 vs. OD: 30.9 ± 3.8, OS: 30.5 ± 3.4). The HEX was significantly decreased in diabetics (OD: 65.5 ± 4.1, OS: 65.4 ± 5 vs. OD: 67 ± 5.2, OS: 67.1 ± 4.6). The CCT was significantly increased in diabetics (OD: 531.6 ± 29.9μm, OS: 538.3 ± 28.9μm vs. OD: 519.2 ± 32.3μm, OS: 526.1 ± 31.2μm). The duration of diabetes showed no significant difference in corneal parameters. However, diabetics with HbA1c <6.5 had significantly increased CCT than those with HbA1c >6.5. Conclusion: There were significant changes in corneal endothelial morphology in patients with type II diabetes.